2006
DOI: 10.1111/j.1399-3054.2006.00627.x
|View full text |Cite
|
Sign up to set email alerts
|

Photostasis and cold acclimation: sensing low temperature through photosynthesis

Abstract: Photosynthesis is a highly integrated and regulated process which is highly sensitive to any change in environmental conditions, because it needs to balance the light energy absorbed by the photosystems with the energy consumed by metabolic sinks of the plant. Low temperatures exacerbate an imbalance between the source of energy and the metabolic sink, thus requiring adjustments of photosynthesis to maintain the balance of energy flow. Photosynthesis itself functions as a sensor of this imbalance through the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
382
0
7

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 484 publications
(397 citation statements)
references
References 95 publications
8
382
0
7
Order By: Relevance
“…However, we found that among the 18 sites where the MAT was <7 • C, lower temperature decreased the CnBE RE but not CnBE GPP (Fig. 4c,e), likely stemming from that the cold-tolerant species were able to maintain photosynthesis at low temperature via photoacclimation in order to balance the energy flow (Ensminger et al, 2006), while soil microbes were inactive.…”
Section: Relative Contribution Of Be To the Iav In C Fluxes At The Ecmentioning
confidence: 75%
“…However, we found that among the 18 sites where the MAT was <7 • C, lower temperature decreased the CnBE RE but not CnBE GPP (Fig. 4c,e), likely stemming from that the cold-tolerant species were able to maintain photosynthesis at low temperature via photoacclimation in order to balance the energy flow (Ensminger et al, 2006), while soil microbes were inactive.…”
Section: Relative Contribution Of Be To the Iav In C Fluxes At The Ecmentioning
confidence: 75%
“…In evergreen conifers, this q I is also associated with the termination of growth and induction of frost hardiness . In this q I state, a reorganization of the photosynthetic apparatus may protect conifer needles by dissipating excess energy as heat independent of a pH gradient (Gilmore and Ball, 2000;Ensminger et al, 2006). Overwintering evergreen conifers seem to be able to shift between the dynamic and the sustained antenna quenching (q O ) modes for dissipating excess energy .…”
mentioning
confidence: 99%
“…Plants have developed a wide range of mechanisms to achieve this balance and to avoid photooxidative damage. This includes adjustments of the Chl and protein concentration, changes in antenna size and organization, stoichiometry and aggregation of components of the photosynthetic apparatus, and a range of alternative energy dissipation pathways (Demmig- Adams et al, 1996;Asada, 1999;Oquist and Huner, 2003;Munekaga et al, 2004;Kanervo et al, 2005;Ensminger et al, 2006). Recently, the carotenoid zeaxanthin in combination with the PSII subunit PsbS has gained interest as both play an important role in the safe thermal dissipation of excess energy via nonphotochemical quenching (NPQ; Li et al, 2000Li et al, , 2002Savitch et al, 2002;Niyogi et al, 2005).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Les basses températures affectent la phase photochimique en réduisant la capacité de transfert des électrons via la chaîne de transporteur d'électrons et réduisent également la fixation du carbone qui s'effectue par le biais de réactions biochimiques dont l'activité diminue avec la température (Ensminger et al, 2006). Cette altération du fonctionnement photochimique peut conduire à l'accumulation de ROS (reactive oxygen species), molécules toxiques pour la plante.…”
Section: Impact Des Basses Températures Sur Le Fonctionnement Photosyunclassified